Nerve growth factor controls GAP-43 mRNA stability via the phosphoprotein ARPP-19 - Irwin, Nina (National Academy of Sciences, 2002)
The membrane phosphoprotein GAP-43 is involved in axon growth and synaptic plasticity. In PC12 pheochromocytoma cells, induction of a neuronal phenotype by nerve growth factor (NGF) is accompanied by a marked increase in GAP-43 levels. NGF regulates GAP-43 expression by altering the half-life of its mRNA. We report here that the phosphoprotein ARPP-19 mediates this regulation. In an NGF-dependent manner, ARPP-19 bound to a region in the 3′ end of GAP-43 mRNA previously found to be important for regulating the half-life of the mRNA. Overexpression of wild-type ARPP-19 in PC12 cells increased the NGF-dependent expression of a reporter construct linked to the critical 3′ region of GAP-43 mRNA. Mutation of serine 104, the site of phosphorylation by protein kinase A in ARPP-19, to either alanine or aspartate abolished this regulation in PC12 cells. These findings demonstrate that ARPP-19 is an important link between NGF signaling and post-transcriptional control of neuronal gene expression.